Frontispiece: Classifying Degraded Modern Polymeric Museum Artefacts by Their Smell. Issue 25 (11th June 2018) - Curran, Katherine; Underhill, Mark; Grau‐Bové, Josep; Fearn, Tom; Gibson, Lorraine T.; Strlič, Matija
Abstract : Plastics Conservation . In their Communication onpage 7336 ff., K. Curran, M. Strlič et al. discuss the feasibility of using volatile organic compound (VOC) detection to assess degradation in modern heritage objects made of plastic.